THE CONDITION OF CORAL REEFS IN PASUMPAHAN ISLAND AT DISTRICT BUNGUS, PADANG CITY, PROVINCE OF WEST SUMATERA - Kiki Harry Wijaya; Thamrin '; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in March 2016 in Pasumpahan Island at district Bungus, Padang city, province of west Sumatera. The purpose of this research was to know the condition of the coral reefs, such as: the percentage of living coral, variety, Uniformity, and domination based on life form of the coral. The method in this research was survey method by using Line Intercept Transect (LIT). It was consisted of three stations where each station was divided into two sub-depth (4 and 8 meters depth). The results show that the form of coral growth consisted of Acropora Branching (ACB), Acropora Encrusting (ACE), Acropora Submassive (ACS), Acropora Digitate (ACD), Acropora Tabulate (ACT), Coral Branching (CB), Coral Massive (CM), Coral Encrusting (CME), Coral Submassive (CS), Coral Foliose (CF), Coral Heliopora (CHL) dan Coral Mushroom (CMR). The condition of coral reefs in Psumpahan Island was good in the dept of 4 meter (60.70%) and in the dept of 8 meter (56.85%). Life form diversiy was moderate (H’ 2.99),while domination was low dominace (C 0.15), as well uniformity (E 0:37).Keywords : Condition, Coral reefs, Pasumpahan Island.